In vivo tests for the detection of resistance to trypanocidal drugs: Tests in mice and in ruminants - Geerts, S.; Ndung'u, J.M.; Murilla, G.; Mbwambo, H.; Sirryangwe, L.; Machila, N.; Delespaux, V.; Brandt, J.; Peregrine, A.S.; McDermott, John J.; Holmes, P.H.; Eisler, M.C. (European Union, 2000)
Besides the in vitro test, two tests are very commonly used for the detection of trypanocidal drug resistance: the tests in mice and in ruminants. Since it has been shown that several parameters such as the number of trypanosomes inoculated and the time of treatment might influence the outcome of the latter tests, there is an urgent need to standardise the protocol of these in vivo tests (Geerts & Holmes, 1998). Standardisation should allow a more reliable comparison of the data. on a temporal and a spatial basis across Africa. Furthermore, there is also a need to simplify the available tests for the detection of drug resistance, particularly the test in mice. Due to the labour-intensive protocols which are currently used, most of the available information on drug resistance is derived from limited numbers of case Reports and does not give any indication of the prevalence of resistance in a region or a country. A simplified screening test should allow to examine representative numbers of trypanosome isolates allowing a better appreciation of the impact of trypanocidal drug resistance in a given area. In this contribution simplified and standardised protocols are proposed for the in vivo detection of drug resistance in mice and in ruminants.